International taxation of income from services under double taxation conventions development, practice, and policy - Castelon, Marta (Series on international taxation ;, 2018)
This book provides an overview of the taxation of income from services under double taxation conventions (DTCs) in major jurisdictions across the world. Especially due to the precipitous growth of the digital economy and thus the increased internationalization of services provisions, the international taxation of services has become a dominant focus in international taxation. This book is a major contribution to the debate about tax reform. It responds to the need for a comprehensive overview of the tax opportunities and risks relating to the provision of international services. With a thorough analysis of the international taxation of income from services over the past two centuries, the author sheds new light on present tax policy debates and develops workable proposals for bringing brick-and-mortar DTCs into the digital reality.